All-Russian Educational Young People's Forum, Seliger - 2010 - S.S. Pronin (Овощи России, 2010)
Having come from all regions of Russian Federation tens of thousands of talented young people gathered together in All-Russian Educational Forum. The Agency for Young People's Affairs was a major organizer of the forum.